Pemberian Hukuman â€œPukulanâ€ dan Pembiasaan Berbahasa Dalam Pendidikan Islam Sebagai Solusi Bagi Orang Tua - Nurdahlia , Dwi Ulfa; Setyowati, Endang (Program Pascasarjana Universitas Ibrahimy, 2017)
The child is a trust given by Allah in His people, there are few things should be noted currently child growth and development. Especially the development of aqidah and moral development (akhlak). Developments relating with aqidah as faith, while morals relating with child behavior. pattern against children educaton operations can be performed non-verbal and verbal. No only firmly embodied in or operating verbal language. But can be also shown operating non-verbal, such as what can be done with how to operate physical punishment. Physical punishment is done by parents like hitting the child, not mean parents is cruel for hitting the hearts of Islamic education denid entry, as long as the beating is done based on the rules has been determined. However. Parents can establish morals (akhlak) children with how do good communication. By using language what mannered. Therefore, important for parents teach about speak politely by hearts early on. With communications using language that good will creates the sponsored children hearts speak, because language has the role of character formation for kid.